All things are connected: Exploring environmental justice and traditional ecological knowledge (TEK) learning through autoethnography - Wendy Griswold (Adult Education Research Conference, 2025)
Autoethnography is methodology utilized for exploring lived experience through cultural phenomena. This roundtable will focus on the researcher’s experiences in learning through indigenous, environmental perspectives as an emerging professional.
Keywords: autoethnography; traditional ecological knowledge; community education; indigenous perspectives; environmental justice